Effect of endogenous gibberellic acid content on physiological and yield related traits in late sown wheat - NAGAR, SHIVANI; SINGH, V P; SINGH, NEERA; DHAKAR, RAJKUMAR; ARORA, AJAY (The Indian Journal of Agricultural Sciences, 2022)
Terminal heat stress is becoming a major factor in limiting wheat production with increasing evidence of heat stress in present scenario of climate change. Gibberellic acid is one of the major plant hormones playing crucial role in plant development from germination to seed development, but there is huge gap in knowledge about its role under heat stress. Present study was conducted in late sown wheat (2014–15) at ICAR-IARI, New Delhi to examine the inter-relationship between gibberellic acid (GA3) level and physiological and yield related traits under heat stress in 40 wheat (Trirtcum aestivum L.) genotypes. Genotypes were categorized into three classes namely tolerant, intermediate and sensitive based on heat stress tolerance ability. The diversity in endogenous GA3 concentration was found among the cultivars. The inverse relationship between GA3 level in flag leaf and tolerance level of genotypes was found in this study through regression analysis (P<0.05). The path analysis showed that GA3 had direct negative influence on test weight under heat stress conditions. Thus, investigations of mechanism of GA3 influence on sink capacity has the potential to develop heat tolerant genotypes and increase wheat production under heat stress.